Plasma phosphorylated‐tau181 is an indicator of early manifestations of neuropsychiatric symptoms in younger subclinical individuals. (20th December 2022) - Gontrum, Eva Q.; Saloner, Rowan; Chan, Brandon; Lago, Argentina Lario; Rojas, Julio C.; Casaletto, Kaitlin B; Kramer, Joel H.
Abstract: Background: Neuropsychiatric symptoms (NPS) can be the first manifestations of Alzheimer's disease (AD), predict faster disease progression, and are more prevalent in early‐onset AD. Plasma P‐tau181 is strongly linked to cognitive impairment due to AD, yet it is unclear whether plasma P‐tau181 similarly relates to NPS in non‐demented adults, and whether this association is age‐dependent. Method: Plasma p‐tau181 concentrations (Quanterix Simoa) were measured in 265 non‐demented adults (212 cognitively unimpaired, 53 mild cognitive impairment; age = 74.4 [7.7], 51.5% female). NPS were measured via the informant‐based Neuropsychiatric Inventory Questionnaire (NPI‐Q) with the total severity score selected for analysis. Linear regression examined NPI‐Q score as a function of plasma P‐tau181, age, and their interaction, covarying for sex and diagnosis. To probe interaction effects, region of significance analyses identified the threshold along the distribution of age at which statistically significant plasma P‐tau181 and NPS associations emerged. Result: NPI‐Q scores ranged from 0–15, with the largest proportion of total scores reflecting anxiety (35%), sleep disturbance (16%), depression (14%), and irritability (14%). In the full sample, higher plasma P‐tau181 related to higher NPI‐Q total severity scores (β = .21, p<0.001). Age moderated the relationship between plasma P‐tau181 and total severity scores (β = ‐.18, p < 0.02) such that higher plasma P‐tau181 was significantly related to higher NPS at younger ages, yet this association was no longer statistically significant after age 72.5. Conclusion: Plasma p‐tau181‐related elevations in NPS were most prominent in mid‐life through early old age (50's to early‐70's), yet this association was attenuated at later age stages, suggesting that the emergence of NPS at younger ages may be more closely linked to tau pathology than late‐life NPS. Importantly, age‐dependent effects on plasma P‐tau181 on NPS were independent of diagnosis, possibly reflecting a unique link between tau pathology and the neurocircuitry underpinning NPS.